Documenting fall episodes: a scoping review - Pernes, Mafalda; Agostinho, Inês; Bernardes, Rafael A.; Belo Fernandes, Júlio; Baixinho, Cristina Lavareda (Frontiers in Public Health, 2023)
Documentation is an important measure for the management of the risk of fall because it concentrates the attention of professionals, raise awareness of the existence of falls’ risk factors and promote action to eliminate or minimize them. This study aims to map the evidence on information to document episodes of falls in older adults. We opted for a scoping review, which followed the JBI protocol for this kind of study. The research question that guided the research strategy was: 'What recommendations emerge from the research on the documentation of falls of the older person?'. The search was performed on the following platforms: MEDLINE, CINAHL, Scopus, and Cochrane Database of Systematic Reviews in January of 2022. The results of the six included manuscripts were extracted, analyzed and a narrative synthesis was made. The documentation of fall episodes should answer the following questions: Who? What? When? Where? How? Doing what? What was said? What were the consequences? What has been done? Despite the recommendations for the documentation of fall episodes as a preventive measure for their recurrence, there are no studies evaluating the cost-effectiveness of this measure. Future studies should explore the association between fall documentation, fall recurrence prevention programs and their impact on the prevalence rate of the second and subsequent falls, as well as the severity of injuries and fear of falling.